Apadana Type Palaces in Classic Architecture of Achaemenid Iran: The Problem of Origins and Evolution - Vergazov, Ramil R. (Actual Problems of Theory and History of Art, 2016)
The article discusses the origins and the evolution of apadana type palaces in Achaemenid architecture (6th–4th centuries B.C.). The Apadana is a specific type of Persian audience palace based on a multi-column hypostyle hall surrounded by porticos on three sides. The genesis of the architectural idea of the Apadana has been analyzed in the context of various influences from ancient Eastern and Greek traditions. The author points out to the most important architectural traditions related to Medes and Anatolian architecture of the 1st millennium B.C. The process of formation of the classical apadana typology can be traced on the examples of early Achaemenid monuments of Cyrus the Great and Cambyses II at Pasargadae and Dasht-i Gohar. The article describes the features of the apadana type palaces at Susa and Persepolis, their hypostyles and façade compositions. In addition, special attention has been paid to the influence of the classical apadana type on further development of Achaemenid architecture (5th–4th enturies B.C.) at Persepolis and in the northern satrapies of the empire. As a result, the consideration of issues on the origin and development of apadana type palaces has allowed us to conclude that their architecture is the conceptual quintessence of the inherently syncretic official art of Darius and Xerxes represented in the palatial ensembles at Susa and Persepolis.
Keywords: Achaemenid Iran; architecture; apadana; audience palace; the era of Darius I; Susa; Persepolis; typology; satrapies